Rat liver microsomal and nuclear activation of methanol to hydroxymethyl free radicals - Castro, Gerardo Daniel (2002)
Recent studies from other laboratories reported that during methanol intoxication lipid peroxidation and protein oxidation in liver occurred. Further, they detected free radicals-PBN adducts in bile and urine of methanol poisoned rats. In this work, we report the presence in liver microsomes and nuclei of NADPH dependent processes of hydroxymethyl (HMet) radical formation. The detection of HMet radicals was performed by GC/MS of the trimethylsilyl derivatives of the PBN (N-tert-butyl-a-phenylnitrone)-radical adducts. The formation of HMet radicals was observed only under nitrogen, in these in vitro conditions. Formation of formaldehyde from methanol was observed in aerobic incubation mixtures containing either microsomes or nuclei but also under nitrogen using microsomes. The latter process was not inhibited by diphenyleneiodonium while the anaerobic microsomal one producing HMet was strongly inhibited by it. This shows that they are independent processes. Results suggest that both, liver nuclei and microsomes are able to generate free radicals during NADPH-mediated methanol biotransformation.